Response of three cultivars of wheat (TriticumaestivumL.) and associated weeds to herbicides - Hussein, Guhdar S.; Mohammed, Bakhtiyar H.; Hussain, Mohammed A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
This experiment was conducted to Study the response of three cultivars of bread wheat and the effect of herbicides on growth and yield of wheat cultivars during the growing season 2014-2015. The experiment comprised three wheat cultivars (Rabiaa, Khemsisi-1, Abugraib-3) and two herbicides treatments Pallas with rates (350, 500 and 650 ml ha-1) and Topic Pallas with three rates (600, 750 and 900 ml ha-1) by using factorial experiment arranged in Randomized Completely Block Design with three replicates. The results showed significant effect of cultivars, herbicides, and cultivars *herbicides concentration in number and dry weight of broad and narrow leaf weeds, 1000-grain weight, number of grain spike -1. The Rabiaacultivar was superiority in grain yield which gave 1929.0 kg ha-1andthe concentration 650 ml ha-1 for both herbicides was more effective in controlling of narrow leaf weeds. The Khemissi-1 cultivar treated with Pallas application at recommended dose (500 ml ha-1) was recorded the lowest number and dry weight of broad leaf weeds 9.33 and 73 g. while the Abugraib-3 cultivar gave (50.28 g) for 1000-grain weight and yield (2016.6 kg ha-1) with Pallas applied at 500 ml ha-1.
Keywords: Herbicide; Topic Pallas; Weed; Narrow and Broad leaf weeds